Pembuatan pupuk organik dari limbah agro industri sebagai alternatif pengganti pupuk sintetis - Komalasari Komalasari; Evelyn Evelyn; Edy Saputra; Syelvia Putri Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Farm and agro wastes from area which population has their livehood from farming and agriculture will result in the environmental and health issues if there is lack treatment on those wastes. One of the solutions to overcome these problems is to convert farm and agro wastes into organic fertilizer, which is produced from living substances weathering (plants and animals). Organic fertilizers are available in the form of solid or liquid and contain a lot of organic materials than nutrient levels, thus can improve plant growth. Other advantages of organic fertilizer are cheaper than synthetic ones, environmentally friendly, and are able to decrease negative effects of chemical fertilizers. Organic fertilizer can be made individually or in group of people. The objectives of this activity are to introduce the knowledge and train rural community of Kecamatan Rambah Hilir, Desa Pasir Utama Kabupaten Rokan Hulu, Provinsi Riau in making organic fertilizer using farm and agro wastes. The methods use in this activity are through socialization and training on making organic fertilizer from farm and agro wastes to Desa Pasir Utama community. Organic fertilizer was made by mixing cow manure with straw cuts, followed by addition of palm sugar activated effective microorganisms 4 (EM4). The mixture was left to incubate for 4 weeks and aerated every three days to allow good fermentation. This community service activity supports government program in encouraging growth of reusing farm and agricultural wastes that will increase agricultural productivity of rural community.